Changes in Inflation and Exchange Rates on Investment Decisions in Sectoral Shares on the Indonesia Stock Exchange - Aldhi Herlando; Sishadiyati Sishadiyati (MediaTrend, 2022)
This research was conducted on the basis of different perceptions regarding the influence of domestic macroeconomics on stock prices. The independent variables used in this study are inflation and exchange rates, while the dependent variable used is the share price of the Indonesia Stock Exchange's Sectoral Index. This study uses monthly data from January 2018 to December 2020. The analysis technique used is multiple regression analysis. There are three findings in this research. First, inflation has a partial effect on most of the sectoral indices except for the Basic Industry Sector Index, the Financial Sector Index and the Trade Sector Index. Second, the Exchange Rate has a partial effect on most of the Sectoral Indices except for the Mining Sector Index and the Trade Sector Index. Third, inflation is the most dominant variable affecting the eight sectoral indices, while the rest is dominated by exchange rates.